PENGARUH METODE TUTOR SEBAYA (PEER TUTORING) DALAM MENINGKATKAN SELF REGULATION MAHASISWA PGSD FKIP UNIVERSITAS QUALITY MEDAN - Gemala Widiyarti; Kevin Ateta Sitepu; Anggi Pebrina Peranginangin (JGK (Jurnal Guru Kita), 2022)
The Influence of Peer Tutoring Method In Improving The Self Regulation of Pgsd Fkip Students Quality University 0f Medan. This study aims to determine the effect of the peer tutoring method in increasing the self-regulation of Elementary School Teacher Education students at FKIP University of Quality Medan. Through tutors or peers, it is hoped that there will be potential behavior through organizing lecture material independently in the form of seeking help and providing assistance during the lecture process. This research is an experimental research using a quasi-experimental design with a total of 40 students as the experimental group and 40 students as the control group. The data collection method is to use a self-regulation scale measuring instrument adapted from the Lailiyah scale (2015). Data analysis technique using Paired samples t test. The reliability of the self-regulation scale is 618 which means it has high reliability. The treatment in this study was carried out in 2 meetings. The research results show that the peer tutoring method can improve student self-regulation. This can be seen from the comparison between the results of the pretest and posttest in the experimental group which experienced an increase. The results of the pretest and posttest are reinforced by the results of the paired samples t-test with a significance level of 0.000 <0.05, because it is smaller than 0.05, then Ho is rejected and Ha is accepted. The difference in the average value of the experimental group was 2.732501, which was greater than the average value of the control group, which was 0.52500, meaning that there was a difference in self-regulation between the control group and the experimental group. The results show that there is an influence on the peer tutoring method in increasing student self-regulation.